Isolated lipstick-like ulceration of the ileocecal valve: A hallmark of cytomegalovirus colitis - Daniel, Fady; Ghaoui, Nohra; Karaoui, Walid R.; Sabatto, Bassel-Zein; Khalifeh, Ibrahim; El-Cheikh, Jean (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Daniel F, Ghaoui N, Karaoui WR, Sabatto BZ, Khalifeh I, El-Cheikh J. Isolated lipstick-like ulceration of the ileocecal valve: A hallmark of cytomegalovirus colitis. Turk J Gastroenterol 2020; 31(3): 274-5.